Molecules to supermolecules and self assembly: a study of some cocrystals of cyanuric acid - Marivel, S.; Suresh, E.; Pedireddi, V. R. (Tetrahedron Letters, 2008)
The preparation and structure elucidation of cocrystals 1a, 1b, 2a- 4a, formed from cyanuric acid (CA) and the aza-donor compounds 4,7-phenanthroline, 1,7-phenanthroline, phenazine and 1, 3 -bis(4-pyridyl) propane, respectively, have been reported. While CA forms different types of self-assembling modes-monomers (la), dimers (1b and 4a) and infinite tapes (2a and 3a)-the recognition of the constituents, however, is through a triple hydrogen-bonding pattern, consisting of an N-H center dot center dot center dot N and two C-H center dot center dot center dot O hydrogen bonds, except in 4a. (C) 2008 Elsevier Ltd. All rights reserved.